Drosophila Syncrip modulates the expression of mRNAs encoding key synaptic proteins required for morphology at the neuromuscular junction - McDermott, Suzanne M. (Cold Spring Harbor Laboratory Press, 2014)
Localized mRNA translation is thought to play a key role in synaptic plasticity, but the identity of the transcripts and the molecular mechanism underlying their function are still poorly understood. Here, we show that Syncrip, a regulator of localized translation in the Drosophila oocyte and a component of mammalian neuronal mRNA granules, is also expressed in the Drosophila larval neuromuscular junction, where it regulates synaptic growth. We use RNA-immunoprecipitation followed by high-throughput sequencing and qRT-PCR to show that Syncrip associates with a number of mRNAs encoding proteins with key synaptic functions, including msp-300, syd-1, neurexin-1, futsch, highwire, discs large, and α-spectrin. The protein levels of MSP-300, Discs large, and a number of others are significantly affected in syncrip null mutants. Furthermore, syncrip mutants show a reduction in MSP-300 protein levels and defects in muscle nuclear distribution characteristic of msp-300 mutants. Our results highlight a number of potential new players in localized translation during synaptic plasticity in the neuromuscular junction. We propose that Syncrip acts as a modulator of synaptic plasticity by regulating the translation of these key mRNAs encoding synaptic scaffolding proteins and other important components involved in synaptic growth and function.